Answer:
x = 2.47 , y = -0.68
Explanation:
let
4x + 13y = -43.................. equation 1
2x - 3y = 7 ..................... equation 2
using substitution method
from equation 2
2x -3y = 7
2x = 7 + 3y
divide both sides by 2
2x/2 = 7 + 3y/2
x = 7 + 3y/ 2.............................. equation 3
put x = x = 7 + 3y/ 2 in equation 1
4x + 13y = -43
4(7 + 3y/2) + 13y = -43
2 ( 7+ 3y) + 13y = -43
12 + 6y + 13y = -43
19y = -43 + 12
19y = - 31
y = -31/19 or -0.68
put y = -0.684 in equation 3
x = 7 + 3y/ 2
x = 7 + 3(-0.684)/2
x = 7- 2.05/ 2
x = 4.947/2
x = 2.47